Lung function improvement on triple modulators: high-resolution, nationwide data from the Danish Cystic Fibrosis Cohort - Christian Leo-Hansen; Daniel Faurholt-Jepsen; Tavs Qvist; Christine Højte; Bibi U. Nielsen; Thomas Bryrup; Esben H. Henriksen; Terese Katzenstein; Marianne Skov; Inger H.M. Mathiesen; Majbritt Jeppesen; Søren Jensen-Fangel; et al. (ERJ Open Research)
Background People living with cystic fibrosis in Denmark had early, universal access to triple modulator treatment with elexacaftor/tezacaftor/ivacaftor. Close monitoring allowed us to assess the impact of treatment on lung function and progression of lung disease in an unselected nationwide cystic fibrosis population from 6 years of age. Methods Data were analysed using linear mixed-effect models to assess changes in levels and annual rates of change (slopes) in percent predicted (pp) forced expiratory volume in 1 s (FEV1), forced vital capacity (FVC) and forced expiratory flow at 25–75% of FVC (ppFEF25–75%) between the 12 months pre-treatment and treatment periods. Subgroup analyses assessed the impact of elexacaftor/tezacaftor/ivacaftor among those with/without previous modulator treatment, normal/mild/moderate/severe lung disease at treatment initiation, children/adults and birth cohorts. Results We included 392 people living with cystic fibrosis with a median (interquartile range) 12 (nine to 15) spirometry measurements per person. The mean (95% CI) improvement in ppFEV1 was 13.0 (11.3–14.6) 12 months after initiation of elexacaftor/tezacaftor/ivacaftor treatment. The annual rate of change improved from −1.4 (−2.1 – −0.6) ppFEV1 in the pre-treatment year to 2.7 (1.8–3.5) ppFEV1 per year during treatment. Similarly, ppFVC increased by 8.0 (7.1–8.9) and FEF25–75% by 19.5 (17.0–21.9). Conclusions Using high-resolution data from a nationwide real-world setting, our study documents the impact of elexacaftor/tezacaftor/ivacaftor on lung function across subgroups based on age, disease severity and treatment history. These findings point towards a new period of consistent lung function improvement among people living with cystic fibrosis on elexacaftor/tezacaftor/ivacaftor.